KAJIAN KUALITAS BAKSO NABATI FORMULASI JAMUR TIRAM (Pleurotus ostreatus) DENGAN PENAMBAHAN DAUN BAYAM (Amaranthus) DAN TEPUNG WIKAU MAOMBO SEBAGAI PRODUK PANGAN FUGSIONAL - Ahmad, Siska; Wahyuni, Sri; rejeki, sri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2018)
ABSTRACT The aim of this study was to determine the effect of oyster mushroom formulations with the addition of spinach leaves and Wikau maombo flour on the sensory assessment of vegetable meatball products. This study used a Completely Randomized Design (CRD) consisting of 5 types of treatments (the addition of oyster mushrooms, spinach leaves and wikau maombo flour) with formulations N1, N2, N3, N4, and N5 samples. In the organoleptic test the color parameters did not significantly affect the aroma and taste parameters and significantly affect on the texture parameters. The content of water, ash, protein, fat and carbohydrate in N1 and N4 samples were 50.98%, 49.81%, 2.41%, 3.07%, 11.90%, 10.25% , 2.20%; 1.53% and 30.11%; 35.75%, respectively. Vegetable meatballs with oyster mushroom formulation with the addition of spinach leaves and wikau maombo flour had nutritional value according to SNI standards and can be received (preferred) by the panelists based on organoleptic assessment. Keywords:Oyster mushrooms, spinach, wikau maombo, vegetable meatballs. ABSTRAK Tujuan penelitian adalah untuk mengetahui pengaruh formulasi jamur tiram dengan penambahan daun bayam dan tepung wikau maombo terhadap penilaian sensoris produk bakso nabati. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL), yang terdiri dari 5 jenis perlakuan (penambahan jamur tiram, daun bayam dan tepung wikau maombo) dengan formulasi N1, N2, N3, N4, dan N5. Pada uji organoleptik parameter warna tidak berpengaruh nyata pada parameter aroma dan rasa serta berpengaruh nyata pada parameter tekstur. Nilai kadar air, abu, protein, lemak dan kadar karbohidrat pada sampel N1 dan N4 berturut-turut sebesar 50,98%;49,81%, 2,41%;3,07%, 11,90%;10,25%, 2,20%;1,53% dan 30,11%;35,75%. Bakso nabati formulasi jamur tiram dengan penambahan daun bayam dan tepung wikau maombo memiliki nilai gizi sesuai standar SNI dan dapat terima (disukai) oleh panelis berdasarkan penilaian organoleptik. Kata kunci: Jamur tiram, Bayam,Wikau maombo, Bakso nabati